Functional Biology and Evolutionary Biology: A Different View of the Origin of Living Things - Hugo Benitez (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
The distinction proposed by Ernst Mayr and François Jacob between functional biology and evolutionary biology is a fundamental key for a clear and conclusive treatment of two problems that, recurrently, are placed in the field of the Philosophy of Biology: that which concerns the possible character teleological of biological explanations and that relative to the autonomy of Biology in relation to Physics and Chemistry. Without supporting an alternative solution for any of these problems, we present that opposition showing its relevance for the treatment of such issues. Our idea is that they should not be raised without specifying which of the two domains of life sciences we are referring to.